\(n\)-alkanol stress-induced cell envelope injury of \(σ^{E}\) promoter in \(Escherichia coli\) - Bui, Huong Thi (Academia Journal of Biology, 2022)
To characterize the cellular stress by n-alkanols with different alkyl chain lengths in Escherichia coli, we investigated how n-alkanols damage cell envelope permeability and whether they enhance the promoter activity of the envelope stress response regulator, σE, by using variants of green fluorescent protein (GFP). By using E. coli cells having GFPuv expressing and localizing in the cytoplasm, the inner membrane, and the periplasm, after exposure to n-alkanols, the fluorescent intensity of GFPuv released from cells was examined. Our data showed that at the similar levels of cell death of about 90–97%, ethanol, a short-chain alkanol, at a concentration of 20% damaged the outer membrane more greatly than the inner membrane, whereas a longer-chain alkanol of pentanol at a concentration of 1.125% damaged both of the outer and inner membranes. Then we investigated the envelope stress response to n-alkanols by σE factor by ratiometric analysis of rpoE promoter activity for the downstream GFPuv expression referenced to that of housekeeping sigma 70 (σ70 ) recognizing lacUV5 promoter for red fluorescent protein (RFP) expression. The results indicated that the relative activity of rpoE promoter by pentanol was much greater than that of ethanol. The degree of its sensitization by rpoE deficiency was much more remarkable for cells treated with pentanol than for those with ethanol. The results suggest that the response of the σE plays a significant role in the membrane integrity and survival of E. coli cells treated with n-alkanols depending on the alkyl chain length of the molecule.